Belarusian-Chinese literary relations: achievements and prospects of the activity of the department of Chinese philology - Khmialnitski, Mikalai M. (Journal of the Belarusian State University. Philology, 2024)
The article examines the current state of the research on Belarusian-Chinese literary connections, considering historical events, the socio-political situation and the literary process of the two countries. The main types of reception of Chinese literature in the Republic of Belarus and the forms of presence and functioning of Belarusian literature in the socio-cultural space of the People’s Republic of China (20th– 21st centuries) are characterised. The role of available translations of works of Belarusian and Chinese writers in the process of mutual perception of peoples is revealed. The contribution to the development of this scientific problem by the staff of the department of Chinese philology of the faculty of philology of the Belarusian State University as well as the prospects of its research in the context of literary dialogue and intercultural communication are defined.